(3TQM GdEQTGOs - (3Jbi GdOjf eXaQs; (3CHj GdeYGdj YHO Gdedc Hf YHO Gddg Hf jhSa GdLhjfj, EeGe GdMQejf,J (B478 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdeHOF GdeYjO GdeaYGd deG jQjO HGH ai CMcGe GdfXQ s
(3BNQgG (B:s
(3hbO jdMb cKjQkG ef GdfGS SBeI ajeG jcdahf EPG OGe hUdi Gddg Ydjg hSde SjOfG hehdGfG eMeO hBdg hUMHg hSde s
(3HgG fXGe GdJYbjHIs
(3hQO GdYfhGf GdCUdi ai cX (B1 / 70s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B160s
Keywords: (3GdJhMjO hGdedd hGdfMds